Sub-national vulnerability and relative location: A case study of South Africa. - Stephanié Rossouw; Don J. Webber (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2012)
Naudé et al. (2009) present an exploration into economic vulnerability from a subnational, district-level perspective. Their paper is an important and timely contribution because it recognises the heterogeneous nature of vulnerability across areas within a country. However, their analysis is aspatial because they do not explicitly account for the relative locations of or the potential for spillovers between contiguous areas. This paper extends the work of Naudé et al. (2009) by i) augmenting their model to take account of spatial contiguity, ii) comparing spatial and aspatial local vulnerability index estimates to illustrate the presence and importance of spatial spillovers between contiguous areas, and iii) enhancing their methodology on the vulnerability intervention index to present results which highlight areas that are performing better and worse than expected. Application of these methods to South African Magisterial District level data reveals a widening urban-rural vulnerability divide.
Keywords: R1; O1; 330; Vulnerability; South Africa